Analisis Pertukaran Barang-Barang Ribawi Pada Pedagang Pasar (Studi Kasus Pasar Tamiang) - Edi Marjan Nasution (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research was conducted at Tamiang Market, Kotanopan District, focusing on the exchange of usury goods by local market participants. This study uses a qualitative descriptive nature, namely research directed at providing symptoms, facts, or events systematically and accurately regarding the characteristics of a particular population or area. This method also uses qualitative descriptive properties to use qualitative descriptive properties to research directly involved in the field/community or a place that is used as the object of study (Tamuang Market). At the same time, the data collection uses interview observations and documentation. The problem in this research is that street vendors and market visitors always exchange ribawi goods (gold for gold and rice for rice) after the big harvest; this exchange is done because traders and market visitors have a brotherly relationship, and this is considered normal. The study results show that this exchange is carried out because it has become a cost ('urf) because both the merchant and the seller have a family relationship whose transaction is consensual. Keywords: usury ribawi’s, exchange, market